THE EVALUATION OF IMPLEMENTATION OF THE USE OF PERSONAL PROTECTIVE EQUIPMENT AND CONSTRUCTION K3 SIGNS - Isror, Maizul; Nugroho, Fajar; Medriosa, Hamdeni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2024)
This research is motivated by the low urgency of occupational health and safety (K3) in construction projects in Indonesia, despite the government having regulated its implementation in the law. This study aims to determine the implementation of Personal Protective Equipment (PPE) in the Construction Project of the Information Center and Library of Padang State University conducted by the company. This research is qualitative in nature. Based on the research results, it is known that, referring to Minister of Public Works and Public Housing Regulation Number 10 of 2021 Regarding the Construction Safety Management System (SMKK), it is concluded that safety helmets, eye protectors, face shields, diving masks, gloves, safety shoes, full-body harnesses, electrical gloves, and respiratory protectors in accordance with Indonesian National Standards (SNI) are available. However, there are no ear protectors, and it is also known that the safety vests and respiratory protective masks do not comply with SNI. Furthermore, it is known that the documents provided by the company are the Construction Safety Plan (RKK), Construction Work Quality Plan (RMPK), Quality Program, Environmental Management and Monitoring Work Plan (RKPPL), and Work Traffic Management Plan (RMLLP). However, the conceptual design document for SMKK is not available. Based on the research results, the researchers suggest that the company should provide complete Personal Protective Equipment (PPE). The company should also install signs at every hazardous location, with signs that are easily visible, clear, and understandable. The company should have complete documents in accordance with the documents required by construction service providers as per Minister of Public Works and Public Housing Regulation Number 10 of 2021 Regarding the Construction Safety Management System (SMKK), and the workers should correctly and consistently use the provided Personal Protective Equipment (PPE) and follow the safety procedures established for each job.